Respuesta :

That would equal to 4 (2x + 2)(x + 2) = 4

Answer:

[tex]\displaystyle (2x+2)(x+2) = 2x^2 + 6x + 4[/tex]

Step-by-step explanation:

We want to express the expression:

[tex]\displaystyle (2x + 2)(x+2)[/tex]

As a trinomial.

To do so, we can expand:

[tex]\displaystyle \begin{aligned} (2x+2)(x+2) &= x(2x+2) + 2(2x+2) \\ \\ &= (2x^2 + 2x) + (4x + 4) \\ \\ &= 2x^2 + 6x + 4\end{aligned}[/tex]

In conclusion, the given expression as a trinomial is:

[tex]\displaystyle (2x+2)(x+2) = 2x^2 + 6x + 4[/tex]